An Exploratory Study Of Personal Financial Planning In Malaysia - Khong, Tan Wei (2004)
This study aims to examine the attitudes of respondents towards various aspects of financial planning, which include money managment, insurance planning, investment planning, retirement planning, and estate planning. The factors most affecting the decision for various aspects of personal financial planning among respondents, and the frequency with which respondents engage in planning for the various aspects of personal financial planning, which include money, insurance, investment, retirement and estate.